2012
DOI: 10.5114/wiitm.2011.30824
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar radiofrequency-induced thermotherapy of haemorrhoids: a new minimally invasive method for haemorrhoidal disease treatment. Early results of a pilot study.

Abstract: IntroductionHaemorrhoidal disease is the most frequent benign anorectal disease. Conservative, minimally invasive and surgical methods are used in the treatment of haemorrhoidal disease. Radiofrequency thermoablation is a popular new technique in the treatment of varicose veins.AimAssessment of the use of the method in the treatment of haemorrhoidal disease using bipolar radiofrequency-induced thermotherapy (RFITT or so-called Celon method).Material and methodsWe used the CelonLab PRECISION (Celon AG medical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Moreover, while a temperature sensor would only provide information on the temperature in the tissue in contact with it (not necessarily the maximum tissue temperature), impedance gives a more complete picture of the characteristics of tissue affected by ablation through the direct relationship between electrical conductivity and temperature. In fact, this technique has been used previously in the management of biliary tumors and venous obstruction or other venous insufficiencies [10][11][12][13]. While we designed our own endoluminal RFA protocol, other studies used commercial devices designed for treating varicose veins (e.g.…”
Section: Technical Feasibilitymentioning
confidence: 99%
“…Moreover, while a temperature sensor would only provide information on the temperature in the tissue in contact with it (not necessarily the maximum tissue temperature), impedance gives a more complete picture of the characteristics of tissue affected by ablation through the direct relationship between electrical conductivity and temperature. In fact, this technique has been used previously in the management of biliary tumors and venous obstruction or other venous insufficiencies [10][11][12][13]. While we designed our own endoluminal RFA protocol, other studies used commercial devices designed for treating varicose veins (e.g.…”
Section: Technical Feasibilitymentioning
confidence: 99%
“…The Rafaelo technique used in this study is radically different by introducing an electrode directly into the internal hemorrhoidal pack. Duben et al [34] described its pilot experience from 2007 to 2017 over 217 patients but with a 35% participation rate at 4 years [35], with other studies including only 74 patients with a 3-month follow-up [32], 70 patients at 6 months [28], 42 patients for 12 months [31], 27 patients for 20 months [30], or 73 patients for 24 months [36]. Thus, the strengths of the presented study are the description of the largest case series reported in France, one of the largest numbers of cases worldwide published and a high and sat- What can patients expect in the long term from radiofrequency thermocoagulation of hemorrhoids on bleeding, prolapse, quality of life, and recurrence: "no pain, no gain" or "no pain but a gain"?…”
Section: Discussionmentioning
confidence: 99%
“…17 However, very little research has been carried out on the link between haemorrhoids and pelvic veins. This study reports the prevalence of haemorrhoids in women with PVR as detected by TVS, as well as the influence of pelvic reflux patterns and severity on haemorrhoids.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a lot of research into haemorrhoids has been directed at the arterial reflux, resulting in haemorrhoidal artery ligation operations 16 (HALOs) or thermal ablation of the artery. 17 However, very little research has been carried out on the link between haemorrhoids and pelvic veins. This study reports the prevalence of haemorrhoids in women with PVR as detected by TVS, as well as the influence of pelvic reflux patterns and severity on haemorrhoids.…”
Section: Introductionmentioning
confidence: 99%